Hubungan Kebijakan Harga dengan Tingkat Hunian Kamar Executive di Hotel Mahkota Graha Tasikmalaya - R Soni Sumali (Yayasan Literasi Sains Indonesia, 2025)
The purpose of this study is to analyze the relationship between pricing policy and the occupancy rate of Executive rooms at the three-star Mahkota Graha Hotel in Tasikmalaya. This study examines several issues, including: how pricing policy is implemented at the Mahkota Graha Hotel, what room occupancy rate has been achieved at the Mahkota Graha Hotel, specifically in 2024, and the extent of the relationship between pricing policy and Executive room occupancy rate at the Mahkota Graha Hotel in Tasikmalaya.The discussion reveals that the implementation of pricing policy at the Mahkota Graha Hotel is differentiated based on market segment. The occupancy rate achieved in 2024 using the pricing policy was 14,708 rooms, while the occupancy rate for Executive rooms was 14,619 rooms. A correlation coefficient analysis of the pricing policy variable and the Executive room occupancy rate revealed a moderate correlation of 0.572. The coefficient of determination indicates that pricing policy influences Executive room occupancy rates at the Mahkota Graha Hotel in Tasikmalaya by 32.72%, while 67.28% is influenced by other factors not examined in this study.